PeningkatanPotensi Ekonomi Lokal Desa Alue Gadeng Gampong Melalui Usaha Pegolahan Durian Menjadi Pancake - Rosmiati, Rosmiati; Awlia, Avivatul; Melisa, Evri; Aini, Helmida; Maulana, Irfan; Nisa, Rauzhatul; Ramadhan, Rizki; Pertiwi, Asih; Arani, Samsuar (MEUSEURAYA - Jurnal Pengabdian Masyarakat, 2024)
This Community Service aims to enhance the knowledge and skills of Alue Gadeng Gampong Village residents in efforts to boost local economic potential through the processing of durian into pancakes. Usually, durians in this village are only consumed or sold as fresh fruits, which causes residents not to get maximum profits from selling the fruit, this is due to the residents' lack of insight and creativity. Therefore, education and training are necessary to process durians into high-value culinary products, such as pancakes, which are currently popular in society. This service uses the Asset-Based Community Development method (ABCD) through five stages of activity:discovery, dream, design, destiny, reflection, and evaluation. The outcome is increased knowledge and awareness of village women to be creative and innovative and utilize available biological resources to enhance their local economic potential.